The Impact of the Perceived Leadership Style on Team Cohesion in Munir Sukhtian Pharmaceuticals (MS Pharma) Company in Jordan - Manal Alnatour,; Mohamad Shehada, (Technium Social Sciences Journal, 2020)
The present research paper intended to explore the impact of the perceived transformational & transactional Leadership styles on team cohesion in Munir Sukhtian Pharmaceutical Company. An electronic questionnaire was sent to 160 employees in different department in MSP in Amman- Jordan. 84 employees completed the adapted version of the multifactor leadership style (rater form) and the Group Environment Questionnaire. Two attributes of each of leader ship styles were measured. For team cohesion, attraction to group and group integration attributes, were assessed regarding both social and task aspects. Results showed significant moderate correlation between leadership style and team cohesion with no difference when it comes to demographic and functional variables.